Tracking and Reporting Outcomes in Medical Marijuana: Establishing Condition Specific State Level Registries - Paul C Langley (University of Minnesota Libraries Publishing, 2019)
In a previous commentary in INNOVATIONS in pharmacy, the question was raised as to the questions legislators should ask for the licensing of medical marijuana dispensaries. The case was made that if dispensaries accept they have a duty of care then they should be required to monitor patients over the course of their treatment with botanical cannabis, including hemp based product, to evaluate the response of patients to therapy. One option would be for individual dispensaries (or owners of multiple licenses and dispensary locations) to adopt a registry format and implement an on-line reporting system by registry staff and patients for the conditions being treated. Unfortunately, under present legislative rules for dispensaries there is no incentive for dispensaries to make the necessary investment. It is also unlikely that legislators would be prepared to mandate a registry requirement. The purpose of this commentary is to offer an alternative solution. Rather than dispensary specific registries, a state-wide low cost registry is proposed where dispensaries are required to log in and track patients with specific conditions. In the case of severe pain, a dispensary would log in patients presenting with this condition and the patient tracked over their course of treatment. A further advantage with a statewide registry is that if a patient visits a different dispensary they can still be tracked as they would be identified by their marijuana card number. The ability to track patients by condition, while still resident in a state, would not only minimize the issue of incomplete records, but would provide a comprehensive, research quality framework for evaluating claims for botanical cannabis. This could then provide feedback to legislators and establish a robust basis for rule making.   Article Type: Commentary